Intercropping changed the soil microbial community composition but no significant effect on alpha diversity - Liu, Jiaying; Zhang, Weixi; Teng, Chao; Pang, Zhongyi; Peng, Yanhui; Qiu, Jian; Lei, Jiawei; Su, Xiaohua; Zhu, Wenxu; Ding, Changjun (Frontiers in Microbiology, 2024)
Enhancing the planning of the forest-agricultural composite model and increasing the efficiency with which forest land is utilized could benefit from a thorough understanding of the impacts of intercropping between forests and agriculture on soil physicochemical properties and microbial communities. Populus cathayana × candansis cv. Xinlin No.1 and Glycine max intercrop soils, along with their corresponding monocrops, were used in this study’s llumina high-throughput sequencing analysis to determine the composition and diversity of soil bacterial and fungal communities. The findings indicated that intercropping considerably raised the soil’s total phosphorus content and significantly lowered the soil’s carbon nitrogen ratio when compared to poplar single cropping. Furthermore, the total carbon and nitrogen content of soil was increased and the soil pH was decreased. The sequencing results showed that intercropping had no significant effect on soil alpha diversity. Intercropping could increase the composition of fungal community and decrease the composition of bacterial community in poplar soil. At the phylum level, intercropping significantly increased the relative abundance of four dominant phyla, i.e., Patescibacteria, Proteobacteria, Patescibacteria and Deinococcus-Thermus. And the relative abundances of only two dominant phyla were significantly increased. It was found that soil total phosphorus and available phosphorus content had the strongest correlation with soil bacterial community diversity, and soil pH had the strongest correlation with soil fungal community diversity.